Inspeksi Korosi Sambungan Las FGHAZ-CGHAZ Menggunakan Metode Magnetic Flux Leakage pada Pipa Penyalur Gas - Ekha Panji Syuryana; Kusharjanto Suhirman (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
The welded joints are important factors that have an influence on the integrity of the pipeline. The microstructure differences in FGHAZ (fine grain heat affected zone) and CGHAZ (coarse grain heat affected zone) may potentially lead to micro galvanic corrosion reactions. Corrosion resistance to the weld section needs to be analyzed by ICDA (internal corrosion direct assessment), ECDA (external corrosion direct assessment) and In-line Inspection (ILI) type MFL (magnetic flux leakage) to mapping the condition of corrosion damage to pipelines on external and internal surfaces. Based on MFL inspection result in gas pipe case study with 28 in x 55 km, 0.500 in wall thickness, API 5L X65 indication of damage to weld joints at kilometer point 13 + 2216, defect orientation at 7:43 h, with 25% depth, axial length 116 mm, 67mm circular width and point kilometer 13 + 2219 defect orientation at 8:22, with a depth of 30%, axial length of 77 mm, 40 mm circular width. This pipeline supplies gas with 98.837% methane and 0.107% CO2 impurities